Erratum: Yuan, W., et al. Genome-Wide Identification of Banana Csl Gene Family and Their Different Responses to Low Temperature between Chilling-Sensitive and Tolerant Cultivars. Plants 2021, 10, 122 - Yuan, Weina; Liu, Jing; Takáč, Tomáš; Chen, Houbin; Li, Xiaoquan; Meng, Jian; Tan, Yehuan; Ning, Tong; He, Zhenting; Yi, Ganjun; Xu, Chunxiang (Plants (Basel, Switzerland), 2021)
The authors wish to make the following corrections to this paper [...].